2020
DOI: 10.4103/ajns.ajns_196_19
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following three-level stand-alone anterior cervical discectomy and fusion: Is plating necessary?

Abstract: Background: Anterior cervical discectomy with fusion (ACDF) is a proven method for the treatment of selected patients. The necessity of use of an anterior plate is controversial. The article aims to assess the fusion rates (FRs) and long-term outcomes following three-level ACDF. Materials and Methods: Data were collected from the medical records of patients operated on due to degenerative cervical disease. All patients were treated with three-level ACDF employing polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A study by Zhang et al [33] in 2018 stated that a lower preoperative JOA score is a risk factor for unsatisfactory outcome after ACDF and a higher occupying ratio contributed to this, wherein a patient with a higher occupying ratio had a higher risk for experiencing reperfusion postoperatively, causing permanent neurologic impairment and poor clinical outcome. Theologou et al [34] in 2020 further suggested the assessment of possible coexistence of lumbar pathologies, wherein this condition may mask the symptoms of CDD, thereby resulting in a bias of clinical outcome. However, it has been said in various literature that the relationship between radiological and clinical outcomes is not yet established [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhang et al [33] in 2018 stated that a lower preoperative JOA score is a risk factor for unsatisfactory outcome after ACDF and a higher occupying ratio contributed to this, wherein a patient with a higher occupying ratio had a higher risk for experiencing reperfusion postoperatively, causing permanent neurologic impairment and poor clinical outcome. Theologou et al [34] in 2020 further suggested the assessment of possible coexistence of lumbar pathologies, wherein this condition may mask the symptoms of CDD, thereby resulting in a bias of clinical outcome. However, it has been said in various literature that the relationship between radiological and clinical outcomes is not yet established [26].…”
Section: Discussionmentioning
confidence: 99%